Concomitant MPZ and MFN2 Gene Variants and Charcot Marie Tooth Disease in a Boy: Clinical and Genetic Analysis—Literature Review. (11th April 2022) - Comella, M.; Collotta, A.; Pavone, V.; Ciccia, L.; Bellinvia, A.; Cerruto, C.; Biondi, M. G. L.; Pisani, F.; Pavone, P.
Abstract : Charcot- Marie- Tooth (CMT) disease includes a group of clinically and genetically heterogeneous neuropathic disorders with an estimated frequency of 1 on 2.500 individuals. CMTs are differently classified according to the age of onset, type of inheritance, and type of inheritance plus clinical features. For these disorders, more than 100 genes have been implicated as causal factors, with mutations in the PMP22 being one of the most common. The demyelinating type (CMT1) affects more than 30% of the CMTs patients and manifests with motor and sensory dysfunctions of the peripheral nervous system mainly starting with slow progressive weakness of the lower extremities. We report here a 12 year- old boy presenting with typical features of CMT1 type, hearing impairment, and inguinal hernia who at the next-generation sequence analysis displayed a concomitant presence of two variants: the c.233 C>T p.Ser 78Leu of the MPZ gene (NM_000530.6) characterized as pathogenetic and the c.1403 G>A p.Arg 468His of the MFN2 gene (NM_014874.3) characterized as VUS. Concomitant variant mutations in CMTs have been uncommonly reported. The role of these gene mutations on the clinical expression and a literature review on this topic is discussed.